Sierra Leone : Request for a Three-Year Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Sierra Leone. (IMF Staff Country Reports; Country Report, 2017)
This paper discusses Sierra Leone's Request for a Three-Year Arrangement under the Extended Credit Facility (ECF). In the near term, this ECF is expected to support important but difficult policies: ending routine foreign exchange auctions and eliminating numerous tax and duty exemptions while increasing infrastructure spending and bolstering the social safety net. The ECF will also catalyze maintenance of external support. In the medium term, the proposed arrangement will provide the framework for structural progress on revenue mobilization, public financial management and financial sector reforms, and increased reserves. The IMF staff supports the authorities' request for the new ECF.